Model Strategi Pengembangan Sistem Pengelolaan Sampah Berkelanjutan Berbasis Rencana Induk Sistem Pengelolaan Sampah (Risps): Studi Kasus Kabupaten Ponorogo - Aliyadi Aliyadi (Journal of Mandalika Social Science, 2026)
Waste management is one of the major challenges in achieving sustainable development. Ponorogo Regency has experienced increasing waste generation that has not been matched by adequate waste management services. The overloaded Mrican landfill and the national policy to eliminate open dumping systems have become important drivers for developing the Regional Solid Waste Management Master Plan (RISPS). This study aims to analyze the existing waste management system and formulate sustainable development strategies. A qualitative descriptive case study approach was applied using document analysis, field observations, and policy review. The results indicate that waste management performance is constrained by technical, institutional, financial, and community participation issues. Recommended strategies include waste reduction at the source, expansion of TPS3R facilities, development of sanitary landfill infrastructure, institutional strengthening, sustainable financing, and public awareness improvement. The proposed model is expected to support local governments in implementing sustainable waste management systems.